Protein transport across the small intestine in food allergy. Issue 1 (3rd December 2013) - Reitsma, Marit; Westerhout, Joost; Wichers, Harry J.; Wortelboer, Heleen M.; Verhoeckx, Kitty C. M.
<x xml:space="preserve">Abstract</x> In view of the imminent deficiency of protein sources for human consumption in the near future, new protein sources need to be identified. However, safety issues such as the risk of allergenicity are often a bottleneck, due to the absence of predictive, validated and accepted methods for risk assessment. The current strategy to assess the allergenic potential of proteins focuses mainly on homology, stability and cross‐reactivity, although other factors such as intestinal transport might be of added value too. In this review, we present an overview of the knowledge of protein transport across the intestinal wall and the methods currently being used to measure this. A literature study reveals that protein transport in sensitised persons occurs para‐cellularly with the involvement of mast cells, and trans‐cellularly via enterocytes, while in non‐sensitised persons micro‐fold cells and enterocytes are considered most important. However, there is a lack of comparable systematic studies on transport of allergenic proteins. Knowledge of the multiple protein transport pathways and which model system can be useful to study these processes may be of added value in the risk assessment of food allergenicity.